Analysis of Nipah Virus Codon Usage and Adaptation to Hosts - Khandia, Rekha; Singhal, Shailja; Kumar, Utsang; Ansari, Afzal; Tiwari, Ruchi; Dhama, Kuldeep; Das, Jayashankar; Munjal, Ashok; Singh, Raj Kumar (Frontiers in Microbiology, 2019)
A recent outbreak of Nipah virus (NiV) in India has caused 17 deaths among people living in districts of Kerala state. Its zoonotic nature as well as high rate of human-to-human transmission has led researchers worldwide to work high for understanding the different aspects of the NiV. We performed a codon usage analysis based on publicly available nucleotide sequences of NiV and its host adaptation along with other members of genus Henipavirus in ten hosts. NiV genome encodes nine open reading frames; and overall, no significant bias in codon usage was observed. Aromaticity of proteins had no impact on codon usage. An analysis of preferred codons used by NiV and the tRNA pool in human cells indicated that NiV prefers codons from a suboptimal anticodon tRNA pool. We observed that codon usage by NiV is constrained by compositional and selection pressures, but not by mutational forces. Parameters that define NiV and host relatedness in terms of codon usage were analyzed, with a codon adaptation index (CAI), relative codon deoptimization index (RCDI), and similarity index calculations; which indicated that, of all hosts analyzed, NiV was best adapted to African green monkeys. A comparative analysis based on relative codon deoptimization index (RCDI) for host adaptation of NiV, Hendra virus (HeV), Cedar virus (CedV) and Hendra like Mojiang virus (MojV) revealed that except dogs and ferrets, all evaluated hosts were more susceptible to HeV than NiV.